Perceived Stress, Cortical GABA, and Functional Connectivity Correlates: A Hypothesis-Generating Preliminary Study - Busler, Jessica N.; Coello, Eduardo; Liao, Huijun; Taylor, Jacob; Zhao, Wufan; Holsen, Laura M.; Lin, Alexander P.; Mahon, Pamela B. (Frontiers in Psychiatry, 2022)
Stress exposures and dysregulated responses to stress are implicated in psychiatric disorders of mood, anxiety, and cognition. Perceived stress, an individual’s appraisal of experienced stress and ability for coping, relates to dysregulated functioning in resting state brain networks. Alterations in GABAergic function, may underlie perceived stress-related functional dysregulation in resting state networks, however, this has not yet been explored. Therefore, the current study examined the association of perceived stress with prefrontal GABA levels, and corresponding resting state functional connectivity (RSFC) alterations. Twelve women and six men, ages 35-61, participated. MR spectroscopy was used to measure brain GABA levels in the anterior cingulate cortex (ACC), left dorsolateral prefrontal cortex (DLPFC), and ventromedial prefrontal cortex (VMPFC). Resting state functional scans acquired at 3 Tesla were used to measure RSFC within and between the default mode (DMN), salience (SN), and central executive networks (CEN), hippocampus, and amygdala. We observed significant negative correlations between total PSS scores and left DLPFC GABA levels (r = -0.62, p = 0.023) and between PSS scores and left lateral prefrontal cortex (LPFC)-right amygdala RSFC (r = -0.57, p = 0.043). Left DLPFC GABA levels and RSFC measures were not significantly correlated (all p > 0.141). These preliminary results support a relationship between perceived stress and GABAergic functioning in a core node of the CEN, an intrinsic network thought to underlie goal-directed attentional processes. Our findings extend previous work suggesting that CEN RSFC is related to perceived stress and may inform treatment strategies to improve outcomes in stress-related conditions.